A multipoint problem for partial integro-differential equations - Vasylyshyn, P. B.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We investigate a multipoint problem for a linear typeless partial differential operator with variable coefficients that is perturbed by a nonlinear integro-differential term. We establish conditions for the unique existence of a solution. We prove metric theorems on lower bounds of small denominators that arise in the course of investigation of the problem of solvability.